2009
DOI: 10.1007/s11426-009-0292-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of block length on the self-assembly of end-capping perfluoroalkyl moieties on the polymer surface

Abstract: Most research on copolymers with fluorinated monomers has focused on the relationship between fluorinated monomer content and the corresponding surface structure. However, the influence of the non-fluorinated block on the surface structure of the copolymer film is unknown. Various molecular weight poly(butyl methacrylates) (PBMA) end-capped with 2-perfluorooctylethyl methacrylate (FMA) units (PBMA-ec-FMA) have been synthesized by atom transfer radical polymerization (ATRP). The effect of the PBMA block length … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Two types of linear copolymers (Figure ), consisting of poly­(methyl methacrylate) (PMMA) end-capped with 2-perfluorooctylethyl methacrylate (FMA) on their single and double terminals were synthesized using atom transfer radical polymerization, as described in our previous publications. The copolymer chain structures were checked by fluorine element analysis, gel permeation chromatography (GPC), and infrared spectroscopy (results not shown). The physical parameters of the fluorinated copolymers are listed in Table .…”
Section: Experimental Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two types of linear copolymers (Figure ), consisting of poly­(methyl methacrylate) (PMMA) end-capped with 2-perfluorooctylethyl methacrylate (FMA) on their single and double terminals were synthesized using atom transfer radical polymerization, as described in our previous publications. The copolymer chain structures were checked by fluorine element analysis, gel permeation chromatography (GPC), and infrared spectroscopy (results not shown). The physical parameters of the fluorinated copolymers are listed in Table .…”
Section: Experimental Sectionmentioning
confidence: 99%
“…Fluoropolymers have attracted great attention due to their many unique properties, including low friction, low adhesion, self-cleaning, and antibacterial effects, which mainly originate from the ordered fluorine moieties at the film surface. Regularly aligned closest-hexagonal-packed −CF 3 groups result in a surface with the lowest critical surface tension ever discovered (∼6 mN/m). , Improvement of the molecular ordering and packing efficiency of the fluorinated groups at the surface are of vital importance in designing thin film materials with superior interfacial performance. Generally, two film-preparation methods, namely, spin-coating and solvent-casting, are utilized to prepare the fluorinated polymer films, and different surface structures are mostly produced using the different film-formation methods. When the solvent-casting method is employed, a well-organized fluorinated surface is normally acquired because the fluorinated moieties assembling in the solution have a relatively long time in which to disassemble and segregate onto the surface due to the slow evaporation of the solvents. In a series of works, it was found that a specific polymer architecture of a nonfluorinated chain end-capped with a few fluorinated units is very efficient in achieving surface migration of the fluorinated units, especially when solvent-casting is applied to fabricate the films. This is most likely due to the high mobility of the chain terminal groups and less entropy penalty for surface segregation of the chain ends. It was reported that the surface energy of the solvent-cast films of poly­(acrylates) end-capped with merely one 2-perfluorooctylethyl methacrylate (FMA) unit can be effectively reduced to a value close to that of the surface constituted by perfectly ordered −CF 3 groups (6.0 mN/m). This means that the fluorinated chain ends overwhelmingly segregate onto the film surface and become closely packed in the course of film solidification by slow evaporation of the solvent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Role of the PODMA block in the enrichment of fluorinated units on the brush surface Both the crystallizability and the flexibility of one of the components of a copolymer are known to affect the segregation of another component with a lower surface free energy. 77,78 The crystallinity of PODMA was considered play an important role in the segregation and the orientation of perfluorinated alkyl groups in the cast films of fluorinated PODMA. 38,39 Since the thicknesses of the Au-PMMA 65 -b-PODMA y -ec-PFMA 2 brushes were around 20 nm, it was difficult to use both XRD and DSC techniques to study their crystallinities.…”
Section: Characterization Of Polymer-grafted Gold Surfacesmentioning
confidence: 99%
“…Further copolymerization of tert-butyl acrylate (t-BA) from the surface of PS-g-TNTs was studied, illustrating the "living" characteristics of the surface-induced ATRP method used in this work. Yan et al also prepared well-defined polystyrene/silica hybrid nanoparticles by the ATRP method.Shen's group research interests are mainly on exploitation and development of new catalysts especially rare earth catalysts and methodologies in polymer synthesis [3][4][5][6]. Discrete ion-pair complexes [Ln(EDBP) 2 (DME)Na(DME) 3 ] [Ln = Er (1), Yb (2), Sm (3)] have been synthesized by the reaction between sodium salt of 2,2′-ethylidene-bis(4,6-ditert-butylphenol)(EDBPH 2 ) and Ln(BH 4 ) 3 ·3THF (Ln = Er, Yb, Sm) followed by centrifugation and recrystalization [3].…”
mentioning
confidence: 99%